UJI COBA LAPANGAN PENANAMAN KEDELAI SEBAGAI TANAMAN SELA ACACIA MANGIUM WILD DI AREAL HTI TANAH ASAM Field experiment of soybean intercrop planting among Acacia mangium willd on acidic soil of the forest estate area - R Sudradjat; Sri Komarayati (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
The purpose of the experiment is to study intercrop planting technique of soybean (var. Willis) on acidic soil among Acacia mangium Willd at HTI Mandiangin, Pekan Baru - Riau.Total area of the experiment covers 0.5 ha, divided into 5 treatment plots of 1000 m2 each. Treatments used in the experiment were: control, lime, lime + anorganic fertilizer, compost and compost + anorganic fertilizer. :Lime. was applied in the order of 2 ton/ha, compost 20 ton/ha and 60 kg urea, 45 kg TSP, 45 kg KCl for 2 period. Rhizogin was used fis biofertilizer to promote growth while Azordin 15 WSC and Dithane M 45 were used as pesticides.The resulls of the experiment for plot 1 (control) showed that the productions of biomass was 383.6 kg/ha, wet pod was 645.4kg/ha, dry pod was 466.7 kg/ha soybean was 275.7 kg/ha, average number of root nodule was 4 and plant heigt was 25.90 cm.Plot ll (acidic soil + lime): the productions of biomass was. 745.8 kg/ha, wet pod was 792 kg/ha, dry pod was 578.6 kg/ha, soybean was 436.5 kg/ha, the number of root nodule was 16 and plant height was 42.38 cm.Plot III (acidic soil +lime + anorganic fenilizer), the productions off biomass was 1331 kg/ha,.wet pod was 1067 kg/ha, dry pod was 805.8 kg/ha, soybean was 525.8kg/ha, the number of root nodule was 17 and plant height was 44.76 cm.Plot IV (acidic soil + compost) : the productions of biomass was 1113.2 kg/ha, wet pod was 1364 kg/ha, dry pod was 963.9kg/ha, soybean was 648 kg/ha, the number of root nodule was 22 and plant height was 38.55 cm.Plot V.(acidic soit+Compost+ anorganic fertilizer): the productions of biomass was 1573 kg/ha, wet pod was 2406.6 kg/ha, dry pod was 1531 kg/ha, soybean was 1060.4 kg/ha, the number of root nodule was 24 and plant height was 55.88 cm.The experiment proved that the range from the highest lo the lowest soybean production was given by compost + anorganic fertilizer(384 %),followed by compost (235%), lime + anorganic fertilizer (190 %), lime (125 %) and control (100 %). It is proved that intercrop planting promote the growth of Acacia mangium Willd i.e: compost + anorganic fertilizer (215 %), lime + anarganic fertilizer (173 %), compost (148 %), lime (163 %) and control (100 %).It is evident that compost has an important role in increasing pH or conducting more nutrients uptake, reduction of A1 toxiclty and eliminating nutrient leaching.